Variations in the architecture and histochemistry of the gelatinous fibers in Eriosema (DC.) Desv. (Leguminosae) species from the Brazilian Cerrado - Piva, Tayeme Cristina [UNESP]; Fortuna-Perez, Ana Paula [UNESP]; Vargas, Wanderleia de [UNESP]; Machado, Silvia Rodrigues [UNESP] (Elsevier, 2020)
G-fibers have been widely studied in tension wood, but few studies are available on aerial and underground organs of shrub and subshrub, specially comparing those organs of the same plant. The goal of this study is to compare the general pattern of G-fibers distribution, and the structure and histochemistry of G-fibers walls between aerial and underground organs in 19 Eriosema taxa occurring in the tropical savanna, locally called cerrado. The samples were processed according to standard techniques in plant anatomy and histochemistry. G-fibers occurred throughout the vegetative body and were exclusively extraxylary in organs with primary growth and extraxylary and xylary in organs with incipient secondary growth. G-fibers were more abundant and had a thicker G-layer in the underground organs. In all the organs analyzed, the G-fibers were identified by the presence of a non-lignified internal translucent layer (G-layer) sometimes occupying the entire lumen of the fiber. The abundance and wide occurrence of G-fibers in the vegetative axis of Eriosema plants may represent an adaptive mechanism and may explain why plants that belong to this genus are able to survive in adverse Cerrado conditions. We suggest that the conditions of the Cerrado environment may stimulate the differentiation of gelatinous fibers in these plants. In addition, the ecophysiological significance of the G-fibers, we emphasize their taxonomic value as a unifying character of the Eriosema genus.
Keywords: Cell wall architecture; Functional significance; Gelatinous fibers; Gelatinous layer; Vegetative axis and underground organs